2018
DOI: 10.20964/2018.02.64
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Ni-P Electroless Coatings on Low-Carbon Steel Substrates Using an Environmentally Friendly Pretreatment

Abstract: This study deposits Ni-P alloy films coatings onto low carbon steel substrates using an electroless process. The coating's morphology and properties, including the hardness, polarization and frictional behavior, are analyzed. A conventional pretreatment that uses roughening and activation steps ensures better adhesion between the Ni-P plated layer and the substrate and renders the substrates catalytic. This study reports an environmentally friendly pretreatment for the substrates: physical sandblasting (using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…10(b) showed that there was mainly Cr segregation. As known to all, Cr promotes ferrite formation [9,10], so the Cr enrichment in local area was the key cause of the δ ferrite. On account of the large size and grain boundary characteristic, the effect of δ ferrite to prevent crack propagation is very small, so the δ ferrite is the the favorable place for crack initiation and propagation.…”
Section: Iumrs International Conference In Asiamentioning
confidence: 91%
“…10(b) showed that there was mainly Cr segregation. As known to all, Cr promotes ferrite formation [9,10], so the Cr enrichment in local area was the key cause of the δ ferrite. On account of the large size and grain boundary characteristic, the effect of δ ferrite to prevent crack propagation is very small, so the δ ferrite is the the favorable place for crack initiation and propagation.…”
Section: Iumrs International Conference In Asiamentioning
confidence: 91%